CORPORATE GOVERNANCE , DEBT POLICY AND PROFITABILITY RELATIONSHIP - Herry Subagyo (Universitas Sains dan Teknologi Komputer, 2020)
This study examines the relationship of Corporate Governance with Debt Policy, and Profitability, especially in corporate that conduct IPOs on the Indonesia Stock Exchange for the 2018-2019 period. Corporate Governance uses proxies of the Board of Commissioners, Independent Commissioners, Institutional Investors, and Insider Ownership which is predicted to affect Debt Policy and Profitability Using a purposive sampling technique, obtained 108 samples, the analyst uses multiple regression with the IBM SPSS 23 program. The findings show that Insider Ownership and the Board of Commissioners have a positive effect on profitability, Institutional Investors and Independent Commissioners are not proven to affect profitability. Corporate governance variables that are proven to influence Debt Policy are Insider Ownership, Institutional Investors, and Independent Commissioners.